Cracking Facebook The Importance of Understanding Technology-Based Communication - Korpijaakko, Maria (Brill, 2020)
This book presents a Facebook study on members of the Cusp Generation, or those born before the "great digital divide" of 1995. This delineation allows for a discussion on the possible socio-cultural implications of Facebook use for people of all ages. Members of the Cusp Generation are in a unique position as "part digital natives" to easily acquire and use new media technologies, while being more critically aware of the personal, social, and cultural effects that may arise from them thanks to having some memory of the pre-digital era. Drawing on identity theories rooted in critical theory and cultural studies, the author shows that there are potential constrictions on people's agency in their Facebook use caused by consumer discourse, Facebook's hyperreal nature and structure, psychological predispositions, and the potential for avatar attachment. In raising concerns over the impacts of technology-based communication, this book explores how the medium of Facebook extends and exacerbates processes of offline social reproduction and discusses how the positive social and political aspects of Facebook can be enhanced.